factorise (x-2y)^2 -6(x-2y) +5

Let (x-2y) =a and -6= b+c and 5=bc
so b and c=-5&-1
as equation (x-2y)-6(x-2y)+5=(x-2y)2 +(-5+(-1))(x-2y)+5 so a2+a(b+c)+ bc=(a+b)(a+c) applied
thus giving(x-2y-5)(x-2y-1) as final answer
  • 1
(X-2Y)²-6(X-2Y)+5


{(X-2Y)²-(X-2Y)-5(X-2Y)+5}
[X-2Y{(X-2Y)-1}-5{(X-2Y)-1}
X-2Y=5
X-2Y=1
OR 
A EASIER METHOD IS THAT YOU CAN TAKE (X-2Y)=A

THEN THAT WOULD BE:
A²-6A+5
A²-A-5A+5
A(A-1)-5(A-1)
A=1
A=5


 
  • 1
I hope it would help you

  • 0
Please find this answer

  • 0
Factorise -4(x-2y)^2+8(x-2y)
 
  • 0
What are you looking for?